2020
DOI: 10.3145/epi.2020.nov.14
|View full text |Cite
|
Sign up to set email alerts
|

How is open access publishing going down with early career researchers? An international, multi-disciplinary study

Abstract: This study explores early career researchers’ (ECRs) appreciation and utilisation of open access (OA) publishing. The evidence reported here results from a questionnaire-based international survey with 1600 participants, which forms the second leg and final year of a four year long, mixed methods, longitudinal study that sought to discover whether ECRs will be the harbingers of change when it comes to scholarly communications. Proceeding from the notion that today’s neophyte researchers, believed to hold mille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 95 publications
2
16
0
2
Order By: Relevance
“…However, awareness and understanding of the process and the benefits of open publishing are not widespread within all academic communities [29][30][31][32]. For example, an international study found that 56% of early career researchers interviewed indicated they published OA, but of the publications listed in the interviewees' Curriculum Vitae, only 8.7% were open [33] (p. 9).…”
Section: The Openness Advantagementioning
confidence: 99%
“…However, awareness and understanding of the process and the benefits of open publishing are not widespread within all academic communities [29][30][31][32]. For example, an international study found that 56% of early career researchers interviewed indicated they published OA, but of the publications listed in the interviewees' Curriculum Vitae, only 8.7% were open [33] (p. 9).…”
Section: The Openness Advantagementioning
confidence: 99%
“…Additionally, higher-ranking faculty members (e.g., full professor over assistant or associate) were more likely to be anti-OA. A newer study by Nicholas et al in 2020 [22] showed that willingness to publish in OA journals may be increasing among early-career researchers, with over two-thirds reporting publishing in OA. However, the finding was strongly tempered by Nicholas' previous research showing incongruity between survey answers and researchers' actual CVs.…”
Section: Views Of Open-access Publishingmentioning
confidence: 99%
“…However, they may share funding sources and research areas with colleagues in STEM, medicine, public health, social work, education, and others. In addition to Dalton et al [2], there are several studies that assess researchers' views and habits on OA in large disciplinary groups, which also found STEM to be more accepting of OA, and arts, humanities, and social sciences exhibiting more concerns [3,4,22]. However, no studies were found that specifically look at psychology researchers or break down disciplines more granularly than as "social sciences".…”
Section: Views Of Open-access Publishingmentioning
confidence: 99%
“…contenidos en abierto son las revistas híbridas. Los datos de la encuesta dirigida a los ECRs en 2019 confirman que son los jóvenes científicos de ciencias de la salud los que más difunden sus resultados en acceso abierto (Nicholas et al, 2020c). El estudio reciente de Xu et al (2020) basado en una encuesta a investigadores chinos señala también diferencias entre disciplinas.…”
Section: Publicar En Abiertounclassified
“…Antes de desgranar los resultados específicos del cuestionario distribuido en español conviene hacer referencia al estudio que analiza los datos totales obtenidos de este cuestionario distribuido a nivel global a los jóvenes investigadores y que pueden seguirse en el trabajo de (Nicholas et al, 2020c). Los resultados muestran que la mayoría de los ECRs han publicado en revistas OA pero que la utilización de estas varía en función de la disciplina y del país.…”
Section: Publicar En Abiertounclassified